Denim dyeing effluent treatment by electrocoagulation for maximum reduction in indigo and sulphur black dye discharge. (7th June 2022) - Mudasir, Maryam; Rehman, Sami Ur; Fahad, Muhammad; Raza, Ifra; Alam, Feroz
Abstract: The waste effluents of two different dyes including one vat dye Indigo and one sulphur dye (Stay Black) were treated using continuous electrocoagulation (EC) technique at a denim dyeing plant. A coagulator reactor of 3 L capacity was designed to treat 7.9 L/h to 65.4 L/h of the dye wastewater. Process parameters like pH, flow rate, number of electrodes and material of electrodes were optimised to obtain maximum decrease in chemical oxygen demand (COD) and colour of the effluents before discharge. It was found that by controlling process parameters, COD can be reduced up to 79% and 90% for low concentrated Indigo and sulphur Stay Black dyes, respectively, with a reduction of colour value 98% and 70%, respectively, while for higher effluent concentrations EC efficiency was reported for 81% and 72.3% colour and COD removal, respectively, for indigo dye and 89.3% and 77.6% colour and COD removal, respectively, for sulphur dye. Hence results of the proposed study could provide important information to design a scale up large reactor unit to commercially apply on denim dyeing discharge and control pollution limits of sulphur and sulphates during denim dyeing.